Editorial - Mostert, Nicky (Journal of Health Informatics in Africa, 2024)
Editorial to JHIA Vol. 11(2024) Issue 3Nicky MostertNelson Mandela University, Port Elizabeth, South Africa The Journal of Health Informatics in Africa (JHIA) is committed to publishing original, high-quality research focused on the application of information and communication technologies (ICTs) in the African healthcare sector. To uphold the integrity and originality of the journal, each submission undergoes a thorough process that includes obtaining a Turnitin report prior to assignment to reviewers. Submissions are only considered for review if their Turnitin similarity index is below 15%. Any manuscript exceeding this threshold is immediately rejected. We strongly encourage authors to ensure that their work is original and has not been published elsewhere before submission to JHIA. Once a paper is accepted for review, it undergoes a rigorous double-blind review process. This may result in either acceptance or rejection. In cases of acceptance, most submissions are subjected to a second round of peer review. Authors are required to revise their manuscripts based on reviewer feedback and resubmit them for further evaluation by the same reviewers. Only once both the reviewers and the editorial team are satisfied with the revisions is the paper formally accepted for publication. This issue features three insightful papers:• Eleke, Nwaneri, Okoronkwo, and Samuel present a comprehensive review comparing paper-based and software-assisted nursing documentation, focusing on data precision and timeliness.• Kigombola and Mahundi explore the use cases, approaches, and challenges associated with the implementation of blockchain technology in the healthcare sectors of low- and middle-income countries.• Mwogosi, Kibusi, and Shaoa share insights into primary healthcare practitioners' perceptions of the effectiveness of electronic health record systems for decision support in Tanzania. I would like to extend my deepest gratitude to the editorial team, authors, and peer reviewers whose hard work has made this issue possible. I also encourage researchers engaged in health informatics to contact me about becoming reviewers for JHIA. The expertise of experienced researchers is crucial to maintaining the high quality of research published in our journal. Thank you for your continued support of JHIA.Nicky MostertDecember 2024